PENGARUH PENERAPAN MODEL PEMBELAJARAN ACTIVE LEARNING TIPE“DYNAMIC TRUE OR FALSE“ TERHADAP HASIL BELAJAR SISWA KELAS X DALAM MATA PELAJARAN MENERAPKAN DASAR-DASAR ELEKTRONIKA PROGRAM KEAHLIAN TEKNIK AUDIO VIDEO DI SMKN 1 BUKITTINGGI - Eko Haryadi; Yasdinul Huda; Hanesman Hanesman (Universitas Negeri Padang, 2014)
This research is motivated by the problem of low learning outcomes in subjects apply the basics of electronics class X Audio Video Engineering Department (TAV) Vocational School (SMK) Bukittinggi School 1, an experimental study using two class is a class that acts as a control and experiment. This study aimed to see whether there is influence learning outcomes after implementing the learning model of Active Learning type Dynamic true or False. The problem in this study is the fact that the field is found in SMKN 1 Bukittinggi, there are many students of class X Audio Video Engineering who scored below the standart of learning outcome minimum completeness criteria in subjects applying the basic fundamentals of electronics set a school that is 75.The population of this research is class X TAV SMKN 1 Bukittinggi TA 2013/2014. The data collected from the test results of a study about the essay as many as 20 items. Data were analyzed using Microsoft Excel to test normality, test homogenity, and test hypothesis. Normality test all values obtained χ2count is smaller than the value χ2 table. Homogenitas test obtained χ2 count< χ2table , atau -1,03 < 14,067. Hypothesis test tcount> ttable yaitu (5,613 >1.697). From the test results of research obtained an average value of student which uses the learning model of Active Learning Type Dynamic true or False is 79,53 while the control group of student who use learning directly lower the 60,78. The results of the hypothesis by using Microsoft Excel in t count found that -1,03 < t table 14,067, so the alternative hypothesis (H1) is accepted or rejected the null hypothesis (H0). This means that on average significantly experimental class learning outcomes greater than the average of the control class learning outcomes. So it can be concluded that the application of Dynamic True or False effect on learning outcomes.Keywords : Active Learning, Dynamic True or False